Synbiotic Adjuvant Therapy in Atopic Dermatitis: Our Experience - Rial Prado M.J. ,; Seoane Rodríguez M, (Journal of Pharmacy and Nutrition Sciences, 2016)
Background: Atopic dermatitis is a disease with a lot of clinical interest because it is the point of attachment between allergic diseases and autoimmune diseases. Probiotics and synbiotics favor the expression of anti-inflammatory Th1 cytokines which produces therapeutic benefits in patients with atopic dermatitis as revealed by recent meta-analysis. Material and Method: Six patients (3 women and 3 men) suffering from moderate atopic dermatitis aged between 16 and 28 years were treated with Bifidobacterium lactis BS01, Lactobacillus rhamnosus LR05 and prebiotic fructo -oligosaccharides (2x109CFU) once daily in a period of four months added to their previously scheduled topical treatment. SCORAD index and atopic dermatitis quality of life test (QoLIAD) prior to treatment and four months after treatment were analyzed. Results: After 4 months of treatment we objectified clinical improvement by reducing the SCORAD index (average of 6 points) and better results in QoLIAD test in 5 of the 6 patients. Previously scheduled medical treatment remained unchanged and no side effect was observed in any of the patients treated. Discussion: Most of our patients treated obtained clinical improvement and in quality of life without adverse effects, this fact support the results of recent papers concluding that the use of probiotics in diary clinical practice is a safe coadyuvant and possibly effective in the treatment of atopic dermatitis.